Law and development perspective on international trade law - Lee, Yong-Shik, 1968-; Law and Development Institute (Cambridge : Cambridge University Press, 2011)
'This book gathers seventeen leading scholars to provide a relevant discussion of major topics of international trade law from the perspective of development'--
'Economic development is the most important agenda in the international trading system today, as demonstrated by the Doha Development Agenda (DDA) adopted in the current multilateral trade negotiations of the World Trade Organization (the Doha Round). This book provides a relevant discussion of major international trade law issues from the perspective of development in the following areas: general issues on international trade law and economic development; and specific law and development issues in World Trade Organization, Free Trade Agreement, and regional initiatives. Although there are publications on trade and development issues, mostly discussing developing countries, few publications deal with law and development issues of international trade law comprehensively in its key areas. This book offers an unparalleled breadth of coverage on the topic and diversity of authorship, as seventeen leading scholars contribute chapters from nine major developed and developing countries, including the United States, Canada, Japan, China (including Hong Kong), South Korea, Australia, Singapore, and Israel'--
Machine generated contents note: Part I. Developing Countries and International Trade: 1. Law and development for lease-developed countries: theoretical basis and regulatory framework for microtrade Yong-Shik Lee; 2. Development disputes in international trade Tomer Broude; 3. Intellectual property rights, trade, and economic development Bryan Mercurio; 4. Trade, border security, and development Maureen Irish; Part II. Law and Development in the World Trade Organization: 5. World Trade Organization and developing countries: reform proposal Yong-Shik Lee; 6. Rediscovering the role of developing countries in GATT/WTO before the Doha Round Faizel Ismail; 7. The WTO dispute settlement from the perspective of developing countries Gary Horlick and Katherine Fennell; 8. Pacific countries in the WTO: accession and accommodation, the reality of WTO accession Andrew Mitchell and Joanne Wallis; Part III. Law and Development in Free Trade Agreements: 9. North-South regional trade agreements: prospects, risks, and legal regulation Moche Hirsch; 10. Free trade agreements: WTO disciplines and development perspectives Mitsuo Matsushita and Yong-Shik Lee; 11. FTAs, developing countries, and human rights conditionality Anthony Cassimatis; 12. Free trade agreement and foreign direct investment: a viable answer for economic development? Yong-Shik Lee; Part IV. Law and Development in Regional Initiatives 13. Islands of prosperity and poverty: a rational trade development policy for economically heterogeneous states Colin Picker; 14. The generalized system of preferences of the United States: does it promote industrialization and economic growth in least developed countries? Caf Dowlah; 15. Economic development of North Korea: call for international trade based development policy and legal reform Yong-Shik Lee, Young-Ok Kim and Hye Seong Mun; 16. Applying the'specificity' test of the WTO subsidy rule in the context of China's foreign investment policies Xiaojie Lu; 17. Non-Conclusion Gary Horlick.
Includes bibliographical references and index.
Keywords: World Trade Organization; Foreign trade regulation; International trade